Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/mrd.21250
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular cathepsin B activity is inversely correlated with the quality and developmental competence of bovine preimplantation embryos

Abstract: Recently, the activity of cathepsins B was found to be correlated inversely with the developmental competence of bovine oocytes. In this study, we investigated (1) the role of intracellular cathepsin B expression and developmental competence as well as the quality of bovine preimplantation embryos, and (2) the effect of cathepsin B inhibitor (E-64) during in vitro culture (IVC) on the development and quality of bovine embryos. After in vitro fertilization (IVF) followed by IVC for 7 days, good and poor quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 28 publications
(34 reference statements)
5
54
1
Order By: Relevance
“…Bettegowda et al (2008) first reported that cumulus cells of low developmental competence oocytes showed higher expression of cathepsin B mRNA than those of high developmental competence oocytes (Bettegowda et al 2008). Moreover, our previous studies clearly showed that cathepsin B activity is inversely correlated with the quality of bovine COCs and embryos by the higher activity and protein expression of cathepsin B in poor-quality in vitro matured oocytes and embryos than in good-quality ones (Balboula et al 2010a(Balboula et al , 2010b. Furthermore, cathepsin B was found to impair the oocyte and embryo developmental competence by possible stimulation of the apoptotic pathway (Balboula et al 2010a(Balboula et al , 2010b.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Bettegowda et al (2008) first reported that cumulus cells of low developmental competence oocytes showed higher expression of cathepsin B mRNA than those of high developmental competence oocytes (Bettegowda et al 2008). Moreover, our previous studies clearly showed that cathepsin B activity is inversely correlated with the quality of bovine COCs and embryos by the higher activity and protein expression of cathepsin B in poor-quality in vitro matured oocytes and embryos than in good-quality ones (Balboula et al 2010a(Balboula et al , 2010b. Furthermore, cathepsin B was found to impair the oocyte and embryo developmental competence by possible stimulation of the apoptotic pathway (Balboula et al 2010a(Balboula et al , 2010b.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, our previous studies clearly showed that cathepsin B activity is inversely correlated with the quality of bovine COCs and embryos by the higher activity and protein expression of cathepsin B in poor-quality in vitro matured oocytes and embryos than in good-quality ones (Balboula et al 2010a(Balboula et al , 2010b. Furthermore, cathepsin B was found to impair the oocyte and embryo developmental competence by possible stimulation of the apoptotic pathway (Balboula et al 2010a(Balboula et al , 2010b. In this study, the significant decrease in TUNEL apoptosis in heat-shocked bovine COCs after the addition of cathepsin B inhibitor (E-64) to the IVM medium clearly showed that cathepsin B has one of the key roles in inducing apoptosis during heat shock of bovine COCs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The primers used for analysis of the relative mRNA expression of the genes cathepsin B (CTSB), placenta-specific 8 (PLAC8), and prostaglandin-endoperoxide synthase 2 (PTGS) as markers for blastocyst quality [38,39], and of the reference genes H 2 A histone family, member Z (H2AFZ) and phosphoglycerokinase (PGK) are summarized in Table 1. Each primer of a pair was located on a Bio-Rad Laboratories, Hercules, CA).…”
Section: Primer Design and Quantitative Pcrmentioning
confidence: 99%
“…It has also been reported that E-64 treatment after IVF followed by IVC for 6 days significantly improved developmental competences and increased number of good quality bovine embryos [23]. On the other hand, Min et al (2014) reported that treatment during IVC with E-64 (0.1 and 0.5 μM) significantly improves developmental rates without any noticeable effect on cleavage rate [24].…”
Section: Discussionmentioning
confidence: 99%